In Vitro Viability and Ultrastructural Changes of Cryopreserved Immature Bovine Oocytes - Myint, Thein (2003)
Several studies have shown that current cryopreservation procedures are severely detrimental to the viability of immature bovine oocytes and permit fertilization and development at a very reduced rate. In this study, a number of experiments were conducted to determine the in vitro viability of frozen-thawed and vitrified-thawed immature bovine oocytes. In vitro viability of frozen-thawed immature bovine oocytes was determined based on cumulus mass expansion, nuclear maturation, cleavage and blastocyst rates. Viability was assessed following experiments conducted using a variety of cooling starting temperatures, seeding temperatures, permeable cryoprotectants and saccharides. Effect of using follicular fluid in the preparation of freezing solution on the viability of immature bovine oocytes was also examined. During freezing, chilling injury and cryoprotective agents impaired the viability of immature oocytes. Among the initial cooling temperatures tested. 30°C yielded the best maturation (34.4%) and cleavage (4.5%) rates and while maturation, cleavage and blastocyst rates from unfrozen oocytes were 86.7%, 69.5% and 17.4%, respectively. As for the permeable cryoprotectants, ethylene glycol was the least toxic compared to propanediol and dimethyl sulphoxide. In the experiment of viability study of oocytes after exposure to freezing solution, significantly better cleavage and blastocyst rates were observed when follicular fluid from > 15-mm follicles was added in freezing solution. However, maturation and cleavage rates fol lowing freezing with follicular fluid were statistically significant. Follicular fluid may have the beneficial effect by protecting oocytes from the toxicity of freezing solution but it may not have enough protective property against freezing per se. The maturation rate of immature oocytes was severely affected when exposed to vitrification solution (39.6%) and vitrifying-thawing procedure (33.9%). However, maturation rate of vitrification solution-exposed oocytes did not differ significantly from that of vitrified-thawed oocytes. These results indicate that the adverse effect on maturation rate is mainly due to vitrification solution rather than vitrification procedure. Any ultrastuctural alterations resulted from freezing and vitrification procedures were investigated using the transmission electron microscopy in order to facilitate a better understanding of the cause of the low viability. Enlarged perivitelline space and fewer microvilli were common ultrastructural alterations that resulted from cryopreservation. Despite impairment on the viability of oocytes, most organelles of cryopreserved oocytes were able to retain their morphology.